ON THE FACTORS AFFECTING THE PRODUCTIVITY OF THE SOUTHERN MAKASSAR STRAIT - Ilahude, Abdul Gani (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1978)
An investigation of the upwelling in the Southern Makassar Strait was conducted by LON (Lembaga Oseanologi Nasional) as part of its research program in ecology and oceanography of the Indonesian waters. It consists of observation on one monitoring station and two oceanographical cruises in the region. The result of the monitoring station indicates clearly the occurrence of upwelling and its effect on the hydrology of the region. During the southeast monsoon the upwelled water causes a decrease in temperature and dissolved oxygen and an increase in salinity, density and nitrate-nitrogen, particularly seen at the lower boundary of the homogeneous layer. During the northwest monsoon the upwelled water is replaced by the Jawa Sea water with high temperature, low oxygen, low salinity, low density, very high phosphate, and high silicate. The observation on the oceanographical cruises reveals the precence of two other types of surface waters in the region. They are the East Kalimantan Coastal Water and the South Sulawesi Coastal Water, each is formed by mixing process of sea water and land drainage along the coast of the two islands respectively. Originally they are characterized by low salinity, low oxygen, high temperature, high phosphate, low nitrate and high silicate. Their salinity and dissolved oxygen increase due to mixing with the upwelled water and the high activity of phytoplankton respectively.